Harry Potter and the Chamber of Secrets - Rowling, J. K.; GrandPre, Mary (New York : Arthur A. Levine Books, an imprint of Scholastic Press, 1999)
When the Chamber of Secrets is opened again at the Hogwarts School for Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been released on the school.
The Worst Birthday -- Dobby's Warning -- The Burrow -- At Flourish and Blotts -- The Whomping Willow -- Gilderoy Lockhart -- Mudbloods and Murmurs -- The Deathday Party -- The Writing on the Wall -- The Rogue Bludger -- The Dueling Club -- The Polyjuice Potion -- The Very Secret Diary -- Cornelius Fudge -- Aragog -- The Chamber of Secrets -- The Heir of Slytherin -- Dobby's Reward.
"Year 2"--Spine.
Sequel to: Harry Potter and the sorcerer's stone.
Sequel: Harry Potter and the prisoner of Azkaban.
940L
Keywords: Potter, Harry; Granger, Hermione (Fictitious character); Weasley, Ron (Fictitious character); Hogwarts School of Witchcraft and Wizardry (Imaginary organization); Wizards; Magic; Schools; England; Fiction; Juvenile works; Fantasy fiction